New Words as a Means of Sustaining Conflict in Serbian Public Discourse - Slijepčević Bjelivuk, Svetlana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
Following the collapse of a canopy at the Novi Sad railway station on November 1, 2024, which caused the death of sixteen people, Serbian public discourse entered a profound social crisis marked by intense polarization. Due to the absence of accountability and the failure to initiate judicial proceedings, the situation initially led to student protests and mass gatherings in solidarity. These were subsequently followed by a range of broader social and political actions undertaken by government representatives with the aim of suppressing the unrest. Within these circumstances, Serbian public discourse witnessed the emergence and increasing circulation of lexical items and expressions such as ćaci, Ćaciland, blokaderi (‘blockaders’), pumpadžija, and similar formations. These expressions primarily functioned as labels employed to discredit political opponents, serving as discursive tools of stigmatization and delegitimization.The aim of this paper is to demonstrate how newly coined words in Serbian public discourse became instruments for sustaining conflict between government representatives and their supporters on the one hand, and students, citizens supporting them, and the opposition on the other. The research corpus was compiled from various sources and using multiple methods, covering the period from November 1, 2024, to November 15, 2025. In view of the unambiguous polarization, the collected material was categorized according to a thematic criterion as a hyperordinate one (primarily based on reference). The lexical-semantic analysis was supplemented with a critical-analytical approach in order to uncover manipulative strategies that, at the level of the lexicon, contributed to maintaining the social crisis. A secondary criterion concerned the use of these lexical items from positions of social power. The analysis confirmed that the trajectory of these words moved from the lexical periphery toward the centre, from individualization to appellativization (illustrated by the lexeme ćaci). It was also shown that expressiveness increased with the emergence of newly coined words and expressions motivated by this lexeme, as well as by blokade (‘blockades’), pumpati (‘to pump’), and similar items. Furthermore, these forms expanded across registers—ranging from colloquial and informal to formal usage, and also in the opposite direction, from formal to colloquial contexts. The research confirmed that newly coined words and expressions unequivocally contribute to the maintenance of polarization, and that they are more frequently created and used by actors with a lower degree of political (and media) power.
Keywords: neologism; crisis discourse; Serbian language